“A graça de deus cumpre associar a elaboração do homem”: projeto de educação familiar na união dos moços católicos e no jornal a imprensa (1931-1942) - Gomes, Jorilene Barros da Silva (2020)
This thesis aims to discuss some publications of the Catholic newspaper A Imprensa, which made clear the intention to induce a religious educational model of the family; it is also intended to highlight the way in which the speeches of the União dos Moços Católicos reproduced this model, in order to meet the prerequisites determined by Catholic dogmas, in Paraíba, between the years 1931 to 1942. Such intention is understood, from the observation that the separation of State and Church generated a series of conflicts that emphasized the country as a secular nation, generating, from the Church's point of view, the evils of modernity. In this sense, we will analyze the newspaper A Imprensa and the speeches mentioned above, to understand how the spread of Catholic faith and instruction occurred, aiming to cure these ills in the capital of Paraíba. To this end, we used the papal encyclicals of Popes Pius IX, Leo XIII, Pius X, Benedict XV, Pius XI and Pius XII, chosen for their orientative and educational character, which guided the clergy and the population in general, according to precepts of the Church, as well as the episcopal documents, with appreciation of the pastoral letters of Dom Leme and Dom Moisés. We will also make use of the documentation from the newspaper A Imprensa, produced between the years 1931 to 1942, as it is the central object of our research, as it disseminated the ideas that the Diocese and the Moços Católicos defended, practiced and lived with society. The analysis of these documents corroborates the idea that Moços Católicos and A Imprensa intended for a religious educational model of family and masculinity in Paraíba.